Desenvolvimento de instrumentos de baixo custo e aplicação de métodos analíticos para monitoramento de poluentes atmosféricos em Uberlândia-MG - Sousa, Danielle da Silva (2023)
Adverse effects resulting from air pollution cause major impacts on the environment, health, safety, and well-being of society. According to data from the State of Global Air, gaseous pollutants - such as ozone (O3) and nitrogen dioxide (NO2) - are considered to have a great effect on human health. The monitoring of atmospheric pollutants is carried out by fixed air quality stations that contain high-cost instruments, which reduces the number of units spread across the Brazilian territory. This work presents the development of low-cost methods and instruments for the quantification of O3 and NO2 gases using different strategies. The first method uses passive sampling and paper filters impregnated with indigotrisulfonate dye for indirect O3 collection and quantification. The reaction between indigo and O3 causes a decrease in absorbance proportional to the amount of O3 present in atmospheric air. The sets of samplers were positioned at four strategic points in the city of Uberlândia with a sampling time of 8 hours, carried out with a frequency of 2 or 3 weeks for 10 months. The second part of the work involved the development of an IoT (Internet of Things) analytical platform for hourly quantification of O3 and NO2 using active sampling. The instrument used a mini pump to suck air and direct it to two flasks, one containing 800 μL of indigotrisulfonate and the other 800 μL of Griess-Saltzman reagent solutions for quantification of O3 and NO2, respectively. All peripherals were operated using an Arduino Uno microcontroller, enabling automation and data transmission of results. The transmittance/absorbance was measured using a specific LED and a digital light sensor (TSL2591) allowing us to obtain the analytical signal immediately after the sampling time. The obtained results were validated with the official data from the CETESB monitoring station and showed adequate concordance with the device. The advantages of the two developed methods demonstrate the ease of use, high potential for creating air quality monitoring networks in various parts of the city, providing valuable information about pollutants, and ensuring safety for the population